An expert system to track dengue fever - Sharifah Hanis, Syed Ahmad (2012)
A computer program capable of performing at a human-expert level in a narrow problem domain area is called an expert system.Expert knowledge is often represented in the form of rules or as data within the computer.Depending upon the problem requirement,these rules and data can be recalled to solve problems.Rule-based expert systems have played an important role in modern intelligent systems and their applications in strategic goal setting,planning,design, scheduling,fault monitoring,diagnosis and so on.Dengue is the most common mosquito-borne viral disease of humans that in recent years has become a major international public health concern.Globally, 2.5 billion people live in areas where dengue viruses can be transmitted.From statistic above,obviously dengue fever became a big issue nowadays because it can bring to death if no action is taken.The main problem is many people cannot ensure whether they are infected by dengue fever or not which make them do nothing as they thought it is only a normal fever.Online diagnosis is becoming popular day by day because in today's world people are so busy,they do not even have enough time to visit a doctor.Dengue Tracking System would help them to have an idea about the disease.Dengue Tracking System is an online system that will help people to detect if they are infected by dengue or not.This would help the doctor, to diagnose the person correctly and provides the right treatment.